Atypical responses to faces during binocular rivalry in early glaucoma - Issashar Leibovitzh, Galia; Trope, Graham E.; Kherani, Irfan N.; Buys, Yvonne M.; Tarita-Nistor, Luminita (Frontiers in Neuroscience, 2023)
Purpose Glaucoma is a progressive optic neuropathy that damages retinal ganglion cells and a neurodegenerative disease as it affects neural structures throughout the brain. In this study, we examined binocular rivalry responses in patients with early glaucoma in order to probe the function of stimulus-specific cortical areas involved in face perception. Methods Participants included 14 individuals (10 females, mean age 65 ± 7 years) with early pre-perimetric glaucoma and 14 age-matched healthy controls (7 females, mean age 59 ± 11 years). The 2 groups were equivalent in visual acuity and stereo-acuity. Three binocular rivalry stimulus pairs were used: (1) real face/house, (2) synthetic face/noise patch, and (3) synthetic face/spiral. For each stimulus pair, the images were matched in size and contrast level; they were viewed dichotically, and presented centrally and eccentrically at 3 degrees in the right (RH) and in the left hemifield (LH), respectively. The outcome measures were rivalry rate (i.e., perceptual switches/min) and time of exclusive dominance of each stimulus. Results For the face/house stimulus pair, rivalry rate of the glaucoma group (11 ± 6 switches/min) was significantly lower than that of the control group (15 ± 5 switches/min), but only in the LH location. The face dominated longer than the house in the LH for both groups. Likewise, for the synthetic face/noise patch stimulus pair, rivalry rate of the glaucoma group (11 ± 6 switches/min) was lower than that of the control group (16 ± 7 switches/min) in the LH, but the difference failed to reach significance. Interestingly, the mixed percept dominated less in glaucoma than in the control group. For the synthetic face/spiral stimulus pair, the glaucoma group had lower rivalry rate at all 3 stimulus locations. Conclusion This study reveals atypical responses to faces during binocular rivalry in patients with early glaucoma. The results may be suggestive of early neurodegeneration affecting stimulus-specific neural structures involved in face processing starting in the pre-perimetric phase of the disease.